2014
DOI: 10.4236/jss.2014.24039
|View full text |Cite
|
Sign up to set email alerts
|

The Differentiated Pricing Strategy or Hotel under Dual-Channel Reservation Forms

Abstract: The modern information network environment largely changed consumer habits. Hotel Reservation way becomes increasingly diversified. By building the traditional and Internet booking ways' demand functions which were linear in self-and cross-price effects and the hotel revenue function, we determine the optimal pricing strategy of the hotel's Internet booking way. The effect of the optimal strategy is also discussed, and numerical simulation verifies that the optimal strategy can greatly improve the hotel revenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…DFP strategy has been one of the sort after strategies in hotel industries for maximising the revenue and increasing CST since the past several years. Xu et al (2014) have developed a mathematical model for the relationship between DFP strategy and HTR and established a positive relationship between these two variables. Abrate et al (2012) conducted a survey in 1000 European hotels and based on the hotel booking data collected from three months to a single day found that DFP is an effective means to enhance the HTR.…”
Section: Relationship Between Dfp and Business Performancementioning
confidence: 99%
See 1 more Smart Citation
“…DFP strategy has been one of the sort after strategies in hotel industries for maximising the revenue and increasing CST since the past several years. Xu et al (2014) have developed a mathematical model for the relationship between DFP strategy and HTR and established a positive relationship between these two variables. Abrate et al (2012) conducted a survey in 1000 European hotels and based on the hotel booking data collected from three months to a single day found that DFP is an effective means to enhance the HTR.…”
Section: Relationship Between Dfp and Business Performancementioning
confidence: 99%
“…GOP per available rooms is basically a performance indicator in a hotel and is given by gross revenue minus the gross expenditure and it is a good performance indicator for the hotel and it can form the basis for pricing (Kapiki et al, 2014). DFP as a concept is selling the same product or service at different price for different customers based on customer type, time of purchase, location, etc., (Xu et al, 2014). PBP is to place the product or service at a certain position relative to that of the competitors' product or service with an intention to reach the targeted customers (Smerichevskyi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to Xu, Zhao, and Xu (2014), the Internet has changed the way people live and purchase goods and services in profound ways. This phenomenon has been especially true for the hotel industry.…”
Section: Introductionmentioning
confidence: 99%
“…Measuring how effective each channel is at driving demand is central to assuring overall performance. Xu, et al (2014) found that with changes in ecommerce, traditional booking has changed from offline to a combination of online and offline.…”
Section: Demandmentioning
confidence: 99%